عصمت چغتائی کے افسانوں میں عورت کا سماجی تصور: THE SOCIAL CONCEPT OF WOMEN IN THE STORIES OF ISMAT CHUGHTAI (Contemporary Journal of Social Science Review, 2025)
The environment in which a person is born and raised shapes his thought. This is why the artist eflects both the positive and negative aspects of society in his art. We all know that the involvement of his family heritage, environment, society and social and political conditions is an essential part of the construction and formation of a person's thought. Therefore, the intellectual development of a writer cannot be studied without keeping these points in mind.Similarly, the environment and society around him have also played a major role in the construction and formation of the intellectual development of Ismat Chughtai. When Ismat Chughtai opened his eyes, he found a respectable and highly educated family. His elder brother Azeem Beg Chughtai played an important role in Ismat's education and upbringing. Ismat got all kinds of comfort and luxuries from his childhood, but a major reason for the lack of education and upbringing of Ismat Chughtai was the fact that he had many brothers and sisters. This is the reason why he was deprived of the love he should have received in his childhood. Yes, there must have been people around him in the form of servants۔Due to the education of his parents, he definitely got mental and intellectual freedom. This is the reason why the free atmosphere of the house in which Ismat was raised promoted boldness, self-reliance and rebellion in his nature from the very beginning. Then the surrounding conditions and deep observation of life also played an important role in the formation of his thoughts